How Long Do Junk Bonds Spend in Default? - Helwege, Jean (Journal of Finance, 1999)
This paper analyzes junk bond defaults during 1980 to 1991 to determine which factors affect the length of time spent in default. Bondholder holdouts are not a significant problem, as firms with proportionately more bonds have shorter default spells. In contrast, bank debt is associated with slower restructurings. Bargaining problems arising from contingent liabilities, lawsuits, and size delay the process, although multiple bond classes do not. Neither information problems nor firm value appear to matter. HLTs do not resolve their defaults at a significantly faster pace. Defaults tend to take less time in the 1990s, despite Drexel's disappearance from the market.